2004
DOI: 10.1124/mol.65.5.1070
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Cell Responses to a Novel GlutathioneS-Transferase–Activated Nitric Oxide-Releasing Prodrug

Abstract: We have used structure-based design techniques to introduce the drug O 2 -[2,4-dinitro-5-(N-methyl-N-4-carboxyphenylamino) phenyl] 1-N,N-dimethylamino)diazen-1-ium-1,2-diolate (PABA/NO), which is efficiently metabolized to potentially cytolytic nitric oxide by the isoform of glutathione S-transferase, an enzyme expressed at high levels in many tumors. We have used mouse embryo fibroblasts (MEFs) null for GST (GST Ϫ/Ϫ ) to show that the absence of GST results in a decreased sensitivity to PABA/NO. Cytotoxicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
120
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 115 publications
(125 citation statements)
references
References 39 publications
(39 reference statements)
4
120
0
1
Order By: Relevance
“…Previous studies by our group observed an in vivo induction of protein nitration by PABA/NO (30). Furthermore, a critical ratio of GSH:PABA/NO is necessary to induce glutathionylation versus nitration in vitro.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies by our group observed an in vivo induction of protein nitration by PABA/NO (30). Furthermore, a critical ratio of GSH:PABA/NO is necessary to induce glutathionylation versus nitration in vitro.…”
Section: Discussionmentioning
confidence: 97%
“…In previous studies, we showed the toxicity of PABA/NO to be significantly diminished in NIH/3T3 cells overexpressing MRP1, with an IC 50 value of 50 versus 11 M in wild-type (Findlay, 2004). We used these cells to address whether PABA/NO-induced S-glutathionylation is independent of toxicity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although NOV-002 treatment did not alter the expression levels of actin, S-glutathionylation modification of the protein increased in a dose-and timedependent manner. S-glutathionylation of actin alters the ratio of F ( filamentous) and G (globular) actin, leading to marked changes in the overall cytoskeletal architecture and concomitant changes in cellular trafficking (25). Using confocal microscopy, we evaluated the cytoskeletal architecture and stress fibers with phalloidin staining (which binds specifically to actin; Fig.…”
Section: Resultsmentioning
confidence: 99%